Blockade of mGluR5 in astrocytes derived from human iPSCs modulates astrocytic function and increases phagocytosis - de Lima, Izabella B. Q.; Cardozo, Pablo L.; Fahel, Julia S.; Lacerda, Juliana P. S.; Miranda, Aline S.; Teixeira, Antônio L.; Ribeiro, Fabiola M. (Frontiers in Immunology, 2023)
TNF-α is essential for induction and maintenance of inflammatory responses and its dysregulation is associated with susceptibility to various pathogens that infect the central nervous system. Activation of both microglia and astrocytes leads to TNF-α production, which in turn triggers further activation of these cells. Astrocytes have been implicated in the pathophysiology of a wide range of neurodegenerative diseases with either harmful or protective roles, as these cells are capable of secreting several inflammatory factors and also promote synapse elimination and remodeling. These responses are possible because they sense their surroundings via several receptors, including the metabotropic glutamate receptor 5 (mGluR5). Under neuroinflammatory conditions, mGluR5 activation in astrocytes can be neuroprotective or have the opposite effect. In the current study, we investigated the role of mGluR5 in hiPSC-derived astrocytes subjected to pro-inflammatory stimulation by recombinant TNF-α (rTNF-α). Our results show that mGluR5 blockade by CTEP decreases the secreted levels of pro-inflammatory cytokines (IL-6 and IL-8) following short rTNF-α stimulation, although this effect subsides with time. Additionally, CTEP enhances synaptoneurosome phagocytosis by astrocytes in both non-stimulated and rTNF-α-stimulated conditions, indicating that mGluR5 blockade alone is enough to drive synaptic material engulfment. Finally, mGluR5 antagonism as well as rTNF-α stimulation augment the expression of the reactivity marker SERPINA3 and reduces the expression of synaptogenic molecules. Altogether, these data suggest a complex role for mGluR5 in human astrocytes, since its blockade may have beneficial and detrimental effects under inflammatory conditions.